INTERFACE DESIGN FOR CONTROL USING COMPUTER stoplight - Indrianto Indrianto Indrianto (JAKSTIK Journal, 2004)
programs of a general nature only, such as: Word, Exel and the lainya.sebenarnya computercan be used widely as a controller or an external regulator, such as traffic light controllers,temperature measurement and the other.Computers communicate with the "outside world" must first pass through the interfacemeans (interface). Interface is a tool to bridge between the computer and the outside world. Inorder for an interface is not a problem inside the computer it is necessary to place a specifiedaddress into the computer interface.The interface is often used in the design is a Programmable Peripheral Interface IC 8255 (PPI8255), because price is cheap and easy to use. Interface inside the computer can not runwithout the software. Software at the traffic light controller is used to mengendlikan trafficlights to match the desired light conditions. So, with that traffic lights may reduce congestionon the roads at junction terutuama.